Otimização aerodinâmica de veículos de reentrada atmosférica - Sandrin, Ederson (2019)
Vehicles submitted to supersonic flow are subjected to high pressure and temperature loads. Thus, the present work has the objective to present a geometry optimized for reentry vehicles in the earth atmosphere. The performance of this will be proven by numerical simulation of the flow to which such geometry is subjected. The flow simulation is executed using the Computational Fluid Dynamics methodology that is based on the implementation of the equations that conduct the phenomenon through numerical models. The NSC2KE source code was used to simulate the flow while the BAMG code was used to create the mesh that discretizes the domain and the geometry. The implementation of the source code used is the finite volume discretization method and the solution domain through unstructured meshes. In the simulated geometries, both laminar and turbulent flow models were used, ruled by the Navier-Stokes equations. The working fluid used in all simulations presented was the atmospheric air, shaped as a perfect and thermally gas.